Candida Infective Endocarditis: A Retrospective Study of Patient Characteristics and Risk Factors for Death in 703 United States Cases, 2015–2019. (18th December 2020) - Huggins, Jonathan P; Hohmann, Samuel; David, Michael Z
Abstract: Background: Candida endocarditis is a rare, sometimes fatal complication of candidemia. Past investigations of this condition are limited by small sample sizes. We used the Vizient clinical database to report on characteristics of patients with Candida endocarditis and to examine risk factors for in-hospital mortality. Methods: This was a multicenter, retrospective cohort study of 703 inpatients admitted to 179 US hospitals between October 2015 and April 2019. We reviewed demographic, diagnostic, medication administration, and procedural data from each patient's initial encounter. Univariate and multivariate logistic regression analyses were used to identify predictors of in-hospital mortality. Results: Of 703 patients, 114 (16.2%) died during the index encounter. One hundred fifty-eight (22.5%) underwent an intervention on a cardiac valve. On multivariate analysis, acute and subacute liver failure was the strongest predictor of death (odds ratio [OR], 9.2; 95% confidence interval [CI], 4.8 –17.7). Female sex (OR, 1.9; 95% CI, 1.2–3.0), transfer from an outside medical facility (OR, 1.8; 95% CI, 1.1–2.8), aortic valve pathology (OR, 2.7; 95% CI, 1.5–4.9), hemodialysis (OR, 2.1; 95% CI, 1.1–4.0), cerebrovascular disease (OR, 2.2; 95% CI, 1.2–3.8), neutropenia (OR, 2.5; 95% CI, 1.3–4.8), and alcohol abuse (OR, 2.9; 95% CI, 1.3–6.7) were also associated with death on adjusted analysis, whereas opiate abuse was associated with a lower odds of death (OR, 0.5; 95% CI, 0.2–0.9). Conclusions: We found that the inpatient mortality rate was 16.2% among patients with Candida endocarditis. Acute and subacute liver failure was associated with a high risk of death, whereas opiate abuse was associated with a lower risk of death. Abstract : Among 703 patients with Candida endocarditis admitted to 179 medical centers, in-hospital mortality was 16.2%. Acute and subacute liver failure was the strongest predictor of in-hospital mortality in this cohort.